2008
DOI: 10.1524/ract.2008.1560
|View full text |Cite
|
Sign up to set email alerts
|

Pu(V) reduction and enhancement of particle-water partitioning by exopolymeric substances

Abstract: Central to understanding the environmental behavior of Pu in vadose- and saturated-zones, as well as waste streams, is the contribution of colloidal natural organic mater (NOM), e.g. , biopolymeric exopolymeric substances (EPS) from Pseudomonas fluorescens Biovar II and geopolymeric humic acids (HA), to Pu speciation. Because Pu(V) and Pu(IV) are present in aquatic systems at sub-pM concentrations, many established techniques for chemical speciation and oxidation state determination are not available. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Many studies argued that Pu(V) aq has weak affinity for mineral surfaces (an implication of higher mobilization). An interpretation that slow reduction of Pu(V) aq to Pu(IV) aq , which has a higher tendency to complex with ≡X-OH sites (X = Al, Fe, and Mn), was usually given (Roberts et al, 2008;Begg et al, 2013;Powell et al, 2014). Instead, much lower mobilization of Pu(V) aq was observed in our transport experiments.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…Many studies argued that Pu(V) aq has weak affinity for mineral surfaces (an implication of higher mobilization). An interpretation that slow reduction of Pu(V) aq to Pu(IV) aq , which has a higher tendency to complex with ≡X-OH sites (X = Al, Fe, and Mn), was usually given (Roberts et al, 2008;Begg et al, 2013;Powell et al, 2014). Instead, much lower mobilization of Pu(V) aq was observed in our transport experiments.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…For instance, Roberts et al 18 found that, at pH 8.2, Pu sorption to silica was decreased if Pu(IV) was pre-equilibrated with humic acid prior to any metal−mineral contact. Blinova et al 51 argued that Pu−FA complexation will result in more mobile Pu(IV) species at higher pH values (i.e., pH 6), where one would expect lower FA sorption and larger FA fractions remaining in solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This finding is in agreement with previous results suggesting that a fraction of Pu(IV) may become "irreversibly" sorbed to silica when Pu is complexed with humic acid prior to metal contact with the mineral phase. 18 This inverse relationship between FA concentration and Pu desorption suggests that, under the given pH conditions, ternary surface complexes are likely more stable than binary Pu−goethite complexes on the goethite surface. This is also in accordance with modeling results, which indicate higher Pu K dT values for Pu sorption in most systems containing FA.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…For sorption experiments, 49 ml of the <1 kDa ultrafiltrate of seawater in a stirred-cell unit was added with 1 ml of noncomplexing Tris-HCl buffer solution to maintain a constant pH of 8.1 and to prevent formation of pseudo-colloids during the addition of spikes (Roberts et al, 2008(Roberts et al, , 2009. For the single-sorbent experiments, 2 mg of inorganic particles was added into the solution while stirring, corresponding to a particle concentration of about 40 mg/l, falling in the concentration range of particles in coastal seawater Yang et al, 2013), but somewhat higher than that in open seawater (Guo et al, 1997).…”
Section: Sorption Experimentsmentioning
confidence: 99%